Teknik Pemeriksaan Colon In Loop Dengan Klinis Ileus Obstruksi Pada Pasien Pediatrik - Alrin Leonanda; Salsabila Aprillia; Dita Rsupitasari; Naufal Fauzan; Rizal Ardianto; Muhammad Faisal Adam (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Ileus Obstruction is a blockage that occurs in the intestinal flow both mechanically and functionally. The imaging examination that is often used to diagnose obstructive ileus is colon in loop. Colon in loop examination is a radiological examination technique to determine the condition of the large intestine by inserting contrast media retrogradely. The colon in loop examination technique is generally carried out using several projections including Antero Posterior (AP), Postero Anterior (PA), Lateral, Right Postero Oblique (RPO), Left Postero Oblique (LPO), Right Antero Oblique (RAO), Left Antero Oblique ( LAO). The contrast medium usually used is Barium Enema or Barium Sulfate (BaSO₄). This article was created using a case study approach to determine effective examination and projection procedures for pediatric Colon In Loop examinations with clinical Ileus Obstruction carried out at the radiology installation of Syarifah Ambami Rato Ebu Hospital, Bangkalan Regency, Madura. This examination was carried out with water soluble contrast media and used two projections, namely AP and Lateral, according to the doctor's request because the patient was a baby and from this projection he could depict the entire colon.